On what basis should we select treatment in clinical psychiatry: a question too obvious to ask?. (April 2020) - Restifo, Sam; Tan, Lemuel Y H
Objective: Given the differences between our profession and the broader set of medical disciplines, a review of the factors to be considered in treatment planning was conducted. Conclusion: Treatment planning in psychiatry is inherently more complicated than in other medical disciplines for various reasons including: a broader range of conceptual models of mental illness and treatment; greater complexities around nosology and diagnosis; the greater limitations of the research evidence base and clinical practice guidelines; and the more substantial impacts of patients' subjectivity and contextual aspects. Diagnosis is generally neither a sufficient nor necessarily the most useful criterion for treatment planning in psychiatry, with a number of other considerations to help guide treatment being outlined.